Politics as a moral problem - Kis, János, 1943- (Central European University Press, 2008)
"The instincts of democratic citizens concerning political morality pull in opposite directions. On the one hand, we tend to think that the norms of political action are more lenient than those of private ethics. But we also believe that politicians are subject to more demanding expectations than ordinary people. Political theory must provide a coherent account of these apparently conflicting beliefs." "According to Janos Kis, the classical doctrine is capable of accounting for the first one, but at the cost of sacrificing the second. The main aim of the book is to show how the two intuitions can be integrated in a unified theory, and what such a theory tells us about the role of moral accountability in democratic politics."--Jacket.